PENGARUH KARAKTERISTIK PEMERINTAH DAERAH DAN TEMUAN AUDIT BPK TERHADAP KINERJA PENYELENGGARAAN PEMERINTAHAN DAERAH (Studi Empiris Pada Pemerintah Kabupaten/Kota Di Provinsi NTB) - Risma Diri Artha; Prayitno Basuki; Alamsyah MT MT (InFestasi, 2015)
This study aimed to examined the effect of the characteristics of the local government and BPK audit findings on the performance of the regional administration of the district/city governments in West Nusa Tenggara Province in 2011-2013. Data were collected by using documentation technique and literature. Tests carried out using multiple linear regression test against all regencies/cities in NTB Province which amounted to 10 (ten) Regency/City among others, West Lombok, Central Lombok, East Lombok, North Lombok, Sumbawa, West Sumbawa, Dompu, Bima, Bima and Mataram. The results showed that the level of regional wealth, the degree of dependence on the central goverment, capital expenditures, leverage and audit findings of no significant effect on the performance of the regional administration, while the size of the local government have a significant effect on the performance of the regional administration in the direction of a positive relationship